User Experiences with Editorial Control in Online Newspaper Comment Fields. (16th March 2018) - Løvlie, Anders Sundnes; Ihlebæk, Karoline Andrea; Larsson, Anders Olof
Abstract : This article investigates user experiences with editorial control in online newspaper comment fields following the public backlash against online comments after the 2011 terror attacks in Norway. We analyze data from a survey of online news consumers focusing on experiences and attitudes towards editorial control set against a spectrum between "interventionist" and "noninterventionist" positions. Results indicate that interventionist respondents rate the quality of online comments as poor, whereas noninterventionist respondents have most often experienced being the target of editorial control measures and feel that editorial control has intensified after the terror attacks. We conclude that newspapers should pay attention to the different needs of participants when devising strategies for editorial control. Media professionals should also consider changes to increase the transparency of moderation practices.